2018
DOI: 10.1038/s41598-018-33348-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coumaphos and imidacloprid on honey bee (Hymenoptera: Apidae) lifespan and antioxidant gene regulations in laboratory experiments

Abstract: The main objective of this study was to test comparatively the effects of two common insecticides on honey bee Apis mellifera worker’s lifespan, food consumption, mortality, and expression of antioxidant genes. Newly emerged worker bees were exposed to organophosphate insecticide coumaphos, a neonicotinoid imidacloprid, and their mixtures. Toxicity tests were conducted along with bee midgut immunohistological TUNEL analyses. RT-qPCR assessed the regulation of 10 bee antioxidant genes linked to pesticide toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 42 publications
5
42
1
4
Order By: Relevance
“…Lack of experimental diet consumption does not appear to explain the results of our HPG investigation. Although mean pollen paste consumption (8.6 mg bee –1 per 3 days, SD = 7.69) was lower in our study compared to some in vitro studies, it was within the same range as Hatjina et al ., who found negative effects of pesticide exposure on HPG development . Similar to Hatjina et al ., mean pollen paste consumption at the start of our experiment, coinciding with HPG development, was significantly ( P < 0.001) elevated, up to 3‐fold greater than overall mean consumption.…”
Section: Discussionsupporting
confidence: 66%
“…Lack of experimental diet consumption does not appear to explain the results of our HPG investigation. Although mean pollen paste consumption (8.6 mg bee –1 per 3 days, SD = 7.69) was lower in our study compared to some in vitro studies, it was within the same range as Hatjina et al ., who found negative effects of pesticide exposure on HPG development . Similar to Hatjina et al ., mean pollen paste consumption at the start of our experiment, coinciding with HPG development, was significantly ( P < 0.001) elevated, up to 3‐fold greater than overall mean consumption.…”
Section: Discussionsupporting
confidence: 66%
“…Our previous study reported a reduction in the development of mandibular and hypopharyngeal glands in nurse honeybees exposed to pyraclostrobin and fipronil individually and in combination 15 . Other previous studies reported different responses of antioxidant system of honeybees exposed to pesticides or natural compounds, and these responses can change based on the age of the bee, time of exposure, dosage, and pesticide group 46,47,54,60,61 .…”
Section: Downregulation Of Antioxidant Enzymes and Increase In Suscepmentioning
confidence: 93%
“…Systemic infections in honey bees could be exacerbated by acaricide, neonicotinoid, or fungicide exposure, which reduces intestinal stem cell proliferation (Forkpah et al, 2014) and increases midgut apoptosis (Gregorc et al, 2018;Carneiro et al, 2019), potentially weakening the gut barrier. Hemocytes also function as phagocytic cells in the honey bee hemolymph; however exposure to neonicotinoids reduces hemocytes phagocytic activity (Walderdorff et al, 2018) and hemolymph antimicrobial activity (Brandt et al, 2016).…”
Section: Pesticides Disrupt Honey Bee Immunitymentioning
confidence: 99%